College Algebra (6th Edition)

Published by Pearson
ISBN 10: 0-32178-228-3
ISBN 13: 978-0-32178-228-1

Chapter 1 - Equations and Inequalities - Exercise Set 1.2: 54

Answer

$x=59$

Work Step by Step

We may substitute the expressions involving x into the equation $y_{1}-y_{2}=-4$ and solve: $(\frac{x+1}{4})-(\frac{x-2}{3})=-4$ $(\frac{3}{3})(\frac{x+1}{4})-(\frac{4}{4})(\frac{x-2}{3})=-4$ $(\frac{3x+3}{12})-(\frac{4x-8}{12})=-4$ $\frac{(3x+3)-(4x-8)}{12}=-4$ $\frac{3x+3-4x+8}{12}=-4$ $\frac{-x+11}{12}=-4$ $(12)(\frac{-x+11}{12})=(12)(-4)$ $-x+11=-48$ $-x=-59$ $x=59$ Because we are dealing with a linear equation in one variable, there is only one answer.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.